Dependency of Conductive Atomic Force Microscopy and Lateral Force Microscopy Signals on Scan Parameters for Zinc Oxide Nanorods - Yang, Yijun; Kim, Kwanlae (Korean Journal of Metals and Materials, 2022)
Conductive atomic force microscopy (C-AFM) is one of the most commonly used characterization techniques for piezoelectric one-dimensional nanomaterials. However, a comprehensive understanding of the effects of certain scan parameters on the C-AFM signals remains elusive. In the present work, the dependency of C-AFM signals on the normal force, scan speed, and Z scanner feedback gain was studied in conjunction with lateral force microscopy (LFM) signals. As the normal force increased, the C-AFM and the LFM signals increased for the following two possible reasons. When larger normal force was applied, ZnO nanorods were more effectively deflected, intensifying the piezoelectric effect. Additionally, the triboelectric effect was enhanced via the increased force of friction between the AFM tip and the ZnO nanorods. When the scan speed increased to 0.5 Hz, the LFM signals and the C-AFM signals increased owing to the enhanced degree of deflection in the ZnO nanorods. However, when exceeding 0.5 Hz, both the LFM signals and the C-AFM signals started to decrease because the AFM tip did not come into contact with the short ZnO nanorods at a high scan speed. Finally, with an increase in the feedback gain to 0.5, both the LFM signals and the C-AFM signals increased. However, when the feedback gain exceeded 1.0, the Z scanner feedback loop was too sensitive to deflect the ZnO nanorod, considerably reducing the total LFM signals. In contrast, the total C-AFM signal showed only a moderate decrease.